Introduction to Programming using Interactive Learning - Krusche, Stephan; Berrezueta-Guzman, Jonnathan (Proceedings / Conference on Software Engineering Education & Training, 2023)
Interactive learning has been highly successful in computer science education, leading to improved planning and execution of programming courses. This is accomplished through the amalgamation of exercises equipped with real-time feedback mechanisms, fostering an environment conducive to iterative performance enhancement. Communication portals facilitate knowledge sharing between students and instructors, while computer-based exams alleviate the instructors' workload.This paper focuses on the implementation of interactive learning in a programming course for first-year computer science students. The course, attended by an aggregate of 70 students, predominantly inexperienced in programming, is detailed, along with the digital resources employed during its development, implementation, and evaluation. This paper contributes to demonstrating the effectiveness of this methodology which showcase promising outcomes in a performance comparison between two courses with varying student numbers. The propitious outcomes emanating from this analysis undergird the proposition for extending this interactive learning methodology to a broader spectrum of computer science curricular offerings.